KADAR VITAMIN DALAM PLASMA DARAH PADA PASIEN PSORIASIS DI KOTA MEDAN - Fardella Lufiana; Yahwardiah Siregar; Ariyati Yosi (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2019)
Psoriasis is a chronic inflammatory disease mediated by the immune system with a prevalence of 2-3% in the world population whose manifestations are found in the skin and other organs. Data on the prevalence of psoriasis is still diverse in several hospitals in Indonesia. Multifactors play a role in the incidence of psoriasis both genetic and environmental. Psoriasis lesions occur due to an imbalance between proliferation and differentiation of keratinocytes. Vitamin D has a role in regulating the balance of the process. Vitamin D is a fat soluble vitamin that can suppress the inflammatory process in psoriasis lesions.This study aimed to determine the frequency distribution of age, sex and levels of 25-Hydroxyvitamin D in blood plasma 44 psoriasis patients.Kadar vitamin D tersebut diukur menggunakan metode ELISA (DBC). The results obtained were the average age of 42-year-old psoriasis patients with the youngest age of 18 years and the oldest at 77 years. Female sex was 56.8% and men were 43.2%.The highest vitamin D level was 59.1 ng / ml and the lowest was 7.3 ng / ml so that it averaged 25.92 ng /ml. Analysis of vitamin D levels produced suficiency (31.8%), insufficiency (31.8%) and deficiency (36.4%).It can be concluded that vitamin D levels in psoriasis patients in Medan city 68.2% have less categories (<29 ng / ml) and most deficiencies at 48-57 years old.